GOOGLE CLASSROOM IN INDONESIAN EFL CLASSES: VOICES FROM HIGH SCHOOL TEACHERS AND STUDENTS - Lia Erisca Debbyanti; Adaninggar Septi Subekti (International Journal of Humanity Studies (IJHS), 2022)
The study was conducted to investigate the extent to which Google Classroom (GC) was used in English as Foreign Language (EFL) instruction at the high school level as well as English teachers' and students' views on the use of GC for the instruction. The study employed a qualitative design involving observations and interviews as the methods of data collection. Three English classes at a private high school in Indonesia were observed. Three teachers of the observed classes and six randomly selected students were interviewed. The interview results were analyzed using Thematic Analysis. The study found that GC was used by teachers to upload assignments, monitor students' progress, and make class announcements. Regarding the teacher and student participants' views on the use of Google Classroom, the study found three themes. First, the features of GC were easy to use. Second, GC facilitated a more organized collection of assignments and learning materials. Third, GC had several limitations including difficulty to upload large files, unorganized notifications, and a limited feature allowing instant messaging. From the findings, pedagogical implications and possible limitations are stated along with suggested directions for further relevant studies.